School Nutrition Directors’ Perceptions of Technology Use in School Nutrition Programs - Pratt, Peggy; Bednar, Caralyn; Kwon, Junehee (My University, 2016)
Purpose/Objectives: This study investigated the types of technology/software currently used by Southwest Region school nutrition directors (SNDs) and assessed their perceptions of barriers to purchasing new technology/software. In addition, the importance of future technology/software acquisitions in meeting school nutrition program (SNP) goals was examined. Methods: A questionnaire was developed by the researchers, validated by an expert panel using the Delphi technique, converted to an online format, and pilot tested. A randomized group of School Nutrition Association SNDs and members of the Academy of Nutrition and Dietetics School Nutrition Services Dietetic Practice Group listserv participated. Participants (N = 111) identified technology/software currently used, their perceived computer skill level, and other demographics. Likert-type scales were used to rate agreement/disagreement with barriers to purchasing new technology/software and the importance of future technology/software acquisitions. Multivariate analyses were used to determine differences in SND ratings according to demographic variables. Results: SNDs who completed the survey used a variety of technology/software. The majority of respondents worked in suburban or metropolitan communities and perceived themselves as having advanced/expert computer skills. Older SNDs, SNDs with less education, and SNDs serving fewer meals per day found inadequate funds, outdated computers, and lack of information technology and administrative support to be barriers to acquiring new technology/software. However, SNDs with higher perceived computer skills (p = .003) and higher education levels (p = .073) were more likely to disagree with these barriers. SNDs with higher perceived computer skills utilized the most technology/software (p = .000) and were more likely to see future technology/software acquisitions (p = .551) as important to meeting SNP goals. Applications to Child Nutrition Professionals: Although technology is widely used by many SNDs, some SNDs have not implemented software applications that could help reduce costs and improve productivity. The school nutrition industry needs influential leaders who can develop local mentorship programs, initiate computer skill building classes, and encourage online training for this group of SNDs.
Citation: Pratt, P., Bednar, C., & Kwon, J. (2012). School nutrition directors’ perceptions of technology use in school nutrition programs. Journal of Child Nutrition & Management, 36(2).